ATRT-25. CHECKPOINT MOLECULE B7-H3 IS HIGHLY EXPRESSED ON ATYPICAL RHABDOID TERATOID TUMOR (ATRT) AND IS A PROMISING CANDIDATE FOR CAR T CELL THERAPY. Issue 2 (22nd June 2018) - Theruvath, Johanna; Graef, Claus-Moritz; Heitzeneder, Sabine; Majzner, Robbie; Mitra, Siddhartha; Cheshier, Samuel H; Mackall, Crystal
Abstract: ATRT are highly malignant brain tumors arising in very young children. The prognosis is extremely poor. Hence new treatments are urgently needed. B7-H3 (CD276) is a member of the B7 family of molecules involved in immune regulation and is over-expressed on a wide variety of solid cancers. We recently created a 4-1BB second-generation CAR targeting B7-H3. To date, there is little data on the most efficacious route of administration of CAR T-cells in malignant brain tumors. The goal of this study was to test the anti-tumor activity of the B7-H3 CAR in highly aggressive ATRT xenograft models and compare intracavitary, intraventricular and intravenous administration in terms of efficacy, toxicity and persistence of CAR T-cells. We observed high expression of B7-H3 on primary ATRT patient samples and all tested cell lines. Administration of a single intracavitary or intraventricular infusion of 1x10 6 B7-H3 CAR T-cells was able to eradicate tumor burden, whereas 1x10 7 B7-H3 CAR T-cells administered intravenously led to similar results. Intravenous administration led to high levels of circulating inflammatory cytokines, which were undetectable following local administration. Animals from all groups were protected from tumor re-challenge and displayed similar numbers of CAR-T-cells in the brain after re-challenge. In summary, B7-H3 represents a promising target for CAR-T cell therapy in ATRT and administration of B7-H3 CAR T-cells is efficacious in eradicating ATRT. Efficacy and persistence of CAR-T-cells appeared similar regardless of the route of administration, however, the risk of systemic toxicity may be reduced following locoregional treatment compared to systemic administration.